Impacto económico y comercial en la importación de pinturas industriales por la aplicación de medidas arancelarias y salvaguardias en el Ecuador - Jácome Orellana, Roger Daniel (2016)
The rnost important in the paint market segment is the arca of architecture, the same despite having restrictions, over time has produccd a considerable incrcase in the number of projects that would help in increased demand paintings. Consolidated in a considerable percentage, political and economic circumstances, distributors, importers, and manufacturers of paints, Iocused on the dornestic market, considering the dynarnism of this market to the rise or increase the number of buildings, demand for paints interior and exterior is consolidated; as is generally known over recent years we have implemented a series of foreign trade policies regarding the implementation of tariffs and safeguards, In the present study, the effects will be analyzed with respcct to safeguards imposed on industrial paints, this incidence will be conducted by reviewing the effect of imports of heading analyzed, additional to that information provided by the Superintendence of Companies will be reviewed, securities and Insurance, this information is related to the financia! statement of the last year available and methodology proposed to serve as a contingency plan for a possible decline in sales will be used…..